HAAO rs3816183 Polymorphisms [T] Increase Anterior/Middle Hypospadias Risk in Southern Han Chinese Population - Liu, Yanqing; Fu, Wen; Fu, Kai; Zuo, Xiaoyu; Jia, Wei; Wang, Ning; Zhang, Yan; Liu, Guochang; Deng, Fuming (Frontiers in Pediatrics, 2022)
Hypospadias is a common congenital external genital malformation characterized by abnormal urethral opening. As a protein coding gene catalyzes the synthesis of quinolinic acid, HAAO has been identified as associated with risk to hypospadias in the Japanese and European population. Thus, our study was designed to elaborate on the mutual association between replicated single-nucleotide polymorphisms (SNPs) and hypospadias in Asia's largest case-control study in the Southern Han Chinese population. Strength of interrelation was evaluated by 95% confidence intervals (CI) and odds ratios (OR). Based on the stratified analysis of hypospadias subtypes, our study found that the HAAO risk allele rs386183[T] enhances the susceptibility for hypospadias among patients with mild/moderate hypospadias subtypes (Adjusted OR = 1.31, 95% CI = 1.05-1.64, P= 0.017). Enhanced risk for the total group of hypospadias could not be demonstrated (OR = 1.20, 95% CI =1.00-1.47, P=0.054). In summary, our study found that the rs3816183[T] polymorphism increases the risk of mild/moderate hypospadias among Southern Han Chinese children.